EVALUASI PENGENDALIAN INTERNAL ATAS PROSEDUR PERTANGGUNGJAWABAN ALOKASI DANA DESA PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN SANGGAU - B51110126, Yulidar Astuti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Financial management of the village should be managed according the principles of financial management accountability, transparant and value for money. For this, the authors conducted a study on the evaluation of internal control over accountability procedures Village Fund Aloocation in service revenue, the financial and asset management of the district area. Aims to determine how the system of internal control over accountability procedures Allocation Fund Village and to determine the factors that impede the delivery of SPJ on DPPKAD in the District. The method of research used qualitative research methods descriptive approach in order to provide an overview as well as facts on the ground to solve the problem and see to what extent the implementation of Goverment Regulation No. 37 of 2007 on Guidelines for Management of Village Finances Properly Implemented. Data analysis tool that i use is the organiational structure, systems flowchart, questionaire internal control, and compliance test. From the evaluation results of the analysis tool known that the internal control procedures of the Village Fund Allocation of responsibility has been very good. Keywords : internal controls, accountability, ADD